DECISIONS OF ROMANIAN LAW COURTS IN CASES CONCERNING THE INTERPRETATION OF ARTICLE 3 (D) OF REGULATION (EC) NO 469/2009 OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL OF 6 MAY 2009, CONCERNING THE SUPPLEMENTARY PROTECTION CERTIFICATE FOR MEDICINAL PRODUCTS - BUCURA IONESCU (Challenges of the Knowledge Society)
The supplementary protection certificate is currently considered to represent an accessory of a national or European patent granted in order to extend the duration of the rights that said patent confers on its owner in respect of an active substance or a combination of active substances. Based on the above-mentioned patent and on the certificate, the owner shall have the exclusive right of manufacturing and commercializing the patented product, as well as the right to oppose to any form of counterfeiting of the patented product. The grant of this protection title for medicaments is regulated on the territory of the European Union by the Regulation (EC) No 469/2009 of the European Parliament and of the Council of 6 May 2009 concerning the supplementary protection certificate for medicinal products (Codified version). The conditions for obtaining the certificate are stipulated under Art. 3. The paper is intended to present the decisions made by the Romanian courts in the cases concerning the controversial interpretation of Art. 3 letter d) of the Regulation, which provides that the valid authorization to place the medicament on the market in accordance with Directive 2001/83/EC or Directive 2001/82/EC, as the case may be, should be the first authorization to place the product on the market as a medicament. At the same time, the paper presents the differences in the approach and the judgment of such cases by OSIM (State Office for Inventions and Trademarks) and by the national courts. The paper aims at analyzing said decisions as compared to the European practice, with a view to identifying solutions for a uniform interpretation of Community legislation at the level of the Romanian courts.